Orofacial Disorders of Patients with End Stage Renal Disease Undergoing Haemodialysis - Gowara, Yohana; Sarsito, Afi S.; Siregar, Parlindungan; Wimardhani, Yuniardini S. (UI Scholars Hub, 2014)
Several orofacial disorders in patients with end stage renal disease (ESRD) undergoing hemodialysis have been reported. However, up to the present, particularly in Indonesia, such data still limited. Objective: the purpose of this study was to assess the orofacial disorders in patients with ESDR undergoing hemodialysis at Cipto Mangunkusumo Hospital, Indonesia. Methods: The study was conducted through observation using a cross-sectional design. The subjects were selected by consecutive sampling. Ninety-three patients fulfilled the inclusion criteria and enrolled in this study. They participated in the structural interview-using questionnaire assessing subjective complaints; clinical examinations; and salivary measurements. Results: Xerostomia (82.8%) dysgeusia (66.7%), metal taste (57%), perioral anesthesia (24.7%) were the common symptoms. Clinical findings consisted of tongue coating (100%), calculus deposits (97.8%), pallor of oral mucous (94.6%), sialosis (75.3%), uremic odor (40,9%), haemorrhagic spot (39.8%), angular cheilitis (37.7%), gingival bleeding (15.1%), and oral candidiasis (3.2%) were also found. Salivary changes showed the increase of salivary viscosity (86%), pH (80.6%), buffer capacity (76.3%) whereas decrease of mucous hydration level (79.6%) and the flow rates of unstimulated (22.6%) and stimulated (31.2%) whole saliva were observed. Conclusion: The findings of orofacial disorders required attention and further comprehensive management to enhance the quality of life of patients with ESDR.